The development of security intelligence in New Zealand, 1945-1957 : a thesis presented in partial fulfilment of the requirements for the degree of Master of Defence Studies at Massey University, Manawatu, New Zealand - Wharton, Miriam L (Massey University, 2012)
This thesis focuses on the development of security intelligence in New Zealand between the end of World War II in 1945 and the formation of the New Zealand Security Service in 1956-57. It provides an overview of how this development occurred at a government, senior executive and senior advisory level. There are three key questions that form its parameters: What were the key events and influences which shaped the development of New Zealand’s security intelligence from a predominantly police-oriented capability in 1945 into an independent capability from 1956-57? Who were the domestic and international parties contributing to that development? What is the significance of this period in New Zealand’s intelligence history? A qualitative and generally chronological methodology is applied to describe the process of maturation that security intelligence in New Zealand underwent during the period in question, beginning with a brief description of the arrangements in place before and during World War II. The majority of the thesis is concerned with describing and analysing how domestic and international influences shaped the progression of a security intelligence capability in New Zealand, culminating in the formation of the Security Service. In doing so it broadens understanding of the state’s intelligence history in the early to mid-twentieth century, while remaining aware of the complexity of intelligence as it is applied within a state context.
Keywords: New Zealand Security Service; Police Force of New Zealand Special Branch; New Zealand; Police; Security service; Intelligence service